Održive kompetencije – izazov za visoko obrazovanje / Sustainable Competencies – A Challenge for Higher Education - Spahić, Ehlimana; Čustović, Enita (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The article analyzes the role of higher education institutions in developing and improving sustainable competencies, particularly emphasizing the presence of sustainable development goals in the bachelor programs of the Faculty of Political Sciences at the University of Sarajevo. The authors have analyzed the compatibility of learning outcomes of bachelor programs with sustainable competencies. This analysis showed that the learning outcomes of the six programs were partially aligned with sustainable competencies. In addition to the analysis of learning outcomes, authors have analyzed the presence of the sustainable development goals in thematic units, and they have found that out of 143 courses, 74 courses contain thematic units related to sustainable development goals. Based on this analysis, it was determined that all sustainable development goals were covered within 74 courses. The research results were used to prepare recommendations for improving bachelor programs.